A statistical study of the low‐altitude ionospheric magnetic fields over the north pole of Venus. Issue 8 (11th August 2015) - Zhang, T. L.; Baumjohann, W.; Russell, C. T.; Villarreal, M. N.; Luhmann, J. G.; Teh, W. L.
Abstract Examination of Venus Express (VEX) low‐altitude ionospheric magnetic field measurements during solar minimum has revealed the presence of strong magnetic fields at low altitudes over the north pole of Venus. A total of 77 events with strong magnetic fields as VEX crossed the northern polar region were identified between July 2008 and October 2009. These events all have strong horizontal fields, slowly varying with position. Using the superposed epoch method, we find that the averaged peak field is about 45 nT, which is well above the average ambient ionospheric field of 20 nT, with a full width at half maximum duration of 32 s, equivalent to a width of about 300 km. Considering the field orientation preference and spacecraft trajectory geometry, we conclude that these strong fields are found over the northern hemisphere with an occurrence frequency of more than 33% during solar minimum. They do not show a preference for any particular interplanetary magnetic field (IMF) orientation. However, they are found over the geographic pole more often when the interplanetary field is in the Venus orbital plane than when it is perpendicular to the orbital plane of Venus. The structures were found most frequently in the −E hemisphere, determined from the IMF orientation. The enhanced magnetic field is mainly quasi perpendicular to solar wind flow direction, and it is suggested that these structures form in the low‐altitude collisional ionosphere where the diffusion and convection times are long.